The Influence of Training and Work Motivation on PT Employee Performance. Indonesian Railways (Persero) Regional Division III Palembang - Asiah, Pitri; Roni, Mukran (SEIKO : Journal of Management & Business, 2023)
This research is based on the condition of employee performance from time to time which is getting wider, so companies must open up new strategies in maintaining and improving employee performance. The core problem in this research is the effect of training and work motivation on the performance of employees of PT. Kereta Api Indonesia (Persero) Regional Division III Palembang. Thus, the purpose of this study was to analyze the influence of training variables (X1), work motivation (X2), and employee performance (Y). Data from this survey research were collected by distributing questionnaires to 35 employee respondents at PT. Kereta Api Indonesia (Persero) Regional Division III Palembang with a saturated sampling technique and the analytical technique used to test the hypothesis is a multiple linear regression analysis technique. The results of this study indicate that training has a positive effect on employee performance and work motivation has a positive effect on employee performance and training and work motivation have a simultaneous effect on employee performance